Using Trichoderma Species in Combination with Cattle Dung as Soil Amendment Improves Yield and Reduces Pre-Harvest Aflatoxin Contamination in Groundnut - Victor Ohileobo Dania; Stephen Ejike Eze (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2020)
Aflatoxin contamination in groundnut constitutes a serious risk to human and animal health. The efficacy of combining five Trichoderma species and cattle dung in the management of aflatoxin-producing Aspergillus flavus under laboratory and field conditions was evaluated. Trichoderma asperellum, T. hamatum, T. viride, T. harzianum and T. pseudokoningii were bioassayed against A. flavus in vitro, while they were applied in combination with cattle dung in the field experiment. A randomized complete block design was used for field treatments with four replications. Trichoderma containing 2.3×108 cfu/gr was applied as seed treatment, while soil application was done using 2.5 kg/ha of sorghum grains as carrier and 5 t/ha cattle dung. Aflatoxin concentration was quantified using high-performance thin-layer chromatography. There was no significant difference among the treatments in the laboratory experiment. However, T. harzianum was the most effective with 72.3% mycelial inhibition of A. flavus. Seed treatment with combination of T. harzianum and cattle dung was most effective in reducing A. flavus soil population to 1.1×103 cfu/gr, while the combination of T. hamatum and cattle dung produced the highest pod yield of 2.7 t/ha, which was significantly higher than carbendazim fungicide. Therefore, integrated approach is recommended in managing aflatoxin contamination in pre-harvest groundnut.